Religious Coping (Rcope) dalam Mengatasi Burnout Akademik Mahasiswa Generasi Z - Ramadhanti, Nisrina Farida; Amalia, Najwa Rizki; Surawan, Surawan (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to analyze the role of Religious Coping (RCOPE), particularly its positive form, in helping Generation Z university students deal with academic burnout in the post-pandemic era. Academic burnout among students has intensified, marked by emotional exhaustion, cynicism toward learning, and reduced academic achievement, influenced by academic, personal, social, and physical factors. Using a descriptive qualitative approach, this study explores students’ in-depth experiences in responding to academic pressures. Data were collected through semi-structured interviews with students experiencing burnout and analyzed using thematic analysis to identify key themes and patterns. The findings reveal that positive RCOPE such as prayer, worship, Qur’anic recitation, and spiritual meaningmaking serves as the most effective strategy, providing emotional calmness, enhancing self-regulation, and restoring learning motivation. Non-religious coping strategies offer only short-term relief, while negative RCOPE risks worsening psychological conditions. Overall, the study demonstrates that positive RCOPE functions as an adaptive mechanism and a resilience foundation that enables students to respond more constructively to academic stress. These results highlight the importance of integrating spiritual-based guidance into higher education support systems to strengthen students’ well-being and academic persistence.